2019
DOI: 10.15407/ugz2019.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in the Spatial Distribution and Environmental Consequences of Pv Farms in Southern Romania

Abstract: All forms of energy generation can have intensive or extensive land use requirements, causing habitat and biodiversity loss in sensitive and diverse ecosystems globally. With the rapid transformation and growth of the energy sector in countries worldwide, understanding the impacts of past practices and charting the trajectory of future development projects is imperative for preventing negative environmental consequences. This dissertation contributes modeling strategies for integrating environmental impacts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 129 publications
(173 reference statements)
0
14
0
Order By: Relevance
“…However, our analysis revealed that 80% were installed at least 500 m from the trees to avoid shading and, consequently, decrease the return on the investment. The main socio-economic impacts of the PV parks that could be assessed using the indicator-based analysis are: distance to roads and settlements, hitherto considered as environmental impacts [5,6,7,14], here considered as supporting infrastructure for the economic investment; land/cover changes and the loss of farmland; and solar electric footprint. The network of national and county roads facilitates the access to areas suitable for the construction of photovoltaic parks; most of investments were built so as to benefit from the existing access roads [5,11,6,7].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our analysis revealed that 80% were installed at least 500 m from the trees to avoid shading and, consequently, decrease the return on the investment. The main socio-economic impacts of the PV parks that could be assessed using the indicator-based analysis are: distance to roads and settlements, hitherto considered as environmental impacts [5,6,7,14], here considered as supporting infrastructure for the economic investment; land/cover changes and the loss of farmland; and solar electric footprint. The network of national and county roads facilitates the access to areas suitable for the construction of photovoltaic parks; most of investments were built so as to benefit from the existing access roads [5,11,6,7].…”
Section: Resultsmentioning
confidence: 99%
“…The main socio-economic impacts of the PV parks that could be assessed using the indicator-based analysis are: distance to roads and settlements, hitherto considered as environmental impacts [5,6,7,14], here considered as supporting infrastructure for the economic investment; land/cover changes and the loss of farmland; and solar electric footprint. The network of national and county roads facilitates the access to areas suitable for the construction of photovoltaic parks; most of investments were built so as to benefit from the existing access roads [5,11,6,7]. For this reason, over 66% of investments in the NWDR are located less than 1 km from roads, which reduces the costs (fast transportation, easy access of the equipment, less and/or no additional investments related to roads).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations